2003
DOI: 10.1046/j.1525-1594.2003.07031.x
|View full text |Cite
|
Sign up to set email alerts
|

A Polyurethane Vascular Access Graft and a Hybrid Polytetrafluoroethylene Graft as an Arteriovenous Fistula for Hemodialysis: Comparison with an Expanded Polytetrafluoroethylene Graft

Abstract: The hPTFEG was considered superior to ePTFEG in terms of being complication-free and had the excellent 2 year secondary patency of 90.9%. TVAG, with a patency equal to that of ePTFEG, could be used immediately after implantation due to the absence of limb edema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 7 publications
4
11
0
1
Order By: Relevance
“…We found that both thrombosis‐free graft survival and cumulative graft survival were similar to those obtained with conventional PTFE grafts. This finding is in keeping with previous studies comparing the two graft types (1,3). In contrast, the cumulative risk of infection was substantially higher with polyurethane grafts than with PTFE grafts, particularly in the subset placed in the thigh.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that both thrombosis‐free graft survival and cumulative graft survival were similar to those obtained with conventional PTFE grafts. This finding is in keeping with previous studies comparing the two graft types (1,3). In contrast, the cumulative risk of infection was substantially higher with polyurethane grafts than with PTFE grafts, particularly in the subset placed in the thigh.…”
Section: Discussionsupporting
confidence: 93%
“…Since enrollment in the randomized study was limited to patients receiving an upper extremity graft (1), it is not clear whether its conclusions can be generalized to polyurethane grafts placed in the thigh. Other published series of polyurethane grafts have reported an infection rate of 3–30% (3–7). These studies varied in the proportion of patients receiving thigh grafts and in the time to first graft cannulation, and lacked appropriate control patients with PTFE grafts.…”
mentioning
confidence: 99%
“…On the other hand, Matsuda et al experienced few thromboses using PTFE. Primary patency rate was also reported to be significantly better in the group with PTFE; however, there was no considerable difference in the secondary patency rate of the two grafts (19). Glickman et al, conversely, demonstrated the PVAG grafts to have similar patency and efficacy when compared with the PTFE grafts in dialysis patients.…”
Section: Discussionmentioning
confidence: 92%
“…It was concluded that PVAG is the graft of choice in patients requiring an urgent, reliable, medium- to long-term hemodialysis access (18). On the contrary, other studies have shown PTFE to be an efficient vascular access for hemodialysis where a primary fistula or brachio-basilic transplantation is not possible (6,17,19). Modarai et al, however, reported a poor patency rate and a high risk of complication (infection and thrombosis) using this graft (20).…”
Section: Discussionmentioning
confidence: 94%
“…11 Because perigraft edema occurs in almost all cases of ePTFE graft implantation, the first puncture of a graft is routinely started more than 14 days after implantation. 12 Therefore, the implantation of paclitaxel-coated vascular grafts may significantly reduce morbidities and provide a novel advantage for early first punctures of grafts through prevention of perigraft edema.…”
Section: E F) the Number Of Inflammatory Cells Was Greater In Samplmentioning
confidence: 99%